The typographic characteristics of the body text in Spanish digital newspapers - Suárez-Carballo, Fernando (2019)
Legibility is a decisive factor to optimize the usability of digital newspapers. In order to achieve this goal and to improve the understanding of the message, it is essential to consider the typographic features of the news body text. Through a quantitative method, this study tries to analyze whether, as seen in print press, Spanish online journals show significant standards in the design of this element, both on desktop and smartphone. The investigation is completed with an analysis of the adaptive strategies of each publication by comparing the visual properties of the body text in these two devices. The research concludes that there is a subtle homogeneity in the typographic characteristics of the body text and important differ-ences in the responsive methods of these publications.